Komitmen organisasi sebagai strategi peningkatan kinerja dan loyalitas karyawan: studi tinjauan literatur - Raharjo, Santosa Budi; Masahere, Usran; Widodo, Wahyu (Universitas Widya Mataram, 2023)
Organizations must pay attention to human resource factors in increasing commitment to the organization to fully optimize the competencies they have. Organizational commitment is a high sacrifice made by employees to the organization and a certain belief in the acceptance of organizational values. This study aims to present a number of study results on strategies for improving employee performance and loyalty through organizational commitment. The research method uses a literature review system with the stages of data analysis compare, contrast, and criticize. The research results show that a high level of commitment from an employee can be one way to minimize the consequences of turnover. Organizational commitment is a reflection of the attitude or behavior of employees towards the company in the form of loyalty and action to achieve the vision, mission, and goals of the organization. Employees can be said to be committed if they have a high commitment to the company, this can be seen by looking at the characteristics of strong trust and support for the goals and values of the company, having a very strong will to work, achieve company goals, and always position themselves as part of the company. Employees with high commitment are able to provide high performance.